The Department of Economics at the University of Chicago, 1947–1982 - Arnold C. Harberger; Sebastian Edwards (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2021)
This paper is about the Department of Economics at the University of Chicago, between 1947 and 1982. The paper has the form of a conversation between the two authors and covers issues such as the existence of a "Chicago School," the Department's governance, the personalities of some well-known members such as Frank Knight, Milton Friedman, and Robert Mundell, teaching, and the "Chicago boys." It also deals with the relation between members of the Department and those of other leading Schools.
Keywords: 330; Chicago School; Milton Friedman; monetarism; Frederik Hayek